PENGARUH PERSEPSI PENDAPATAN, PENDIDIKAN, DAN JUMLAH ANGGOTA KELUARGA TERHADAP KESEJAHTERAAN KELUARGA PERSPEKTIF MAQASHID ASY-SYARIAH - rindiani; Kusnadi, iwan; Sulastri (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
This study aims to determine whether there is a positive and significant influence of income, education, and family size, both partially and simultaneously, on family welfare from the perspective of Maqashid Asy-Syariah in Sebayan Village. This research employs a quantitative approach with a causal associative nature. The population in this study consists of 929 households, and the sample size was determined using Roscoe's theory, resulting in a sample of 40 respondents. The type of data used is primary data obtained from the results of a questionnaire. The ordinal data collected was then converted into interval data. Subsequently, the data was processed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS 23. The research results indicate that, partially, there is no positive and significant influence of income on family welfare, as evidenced by the t-value < t-table (1.724 < 2.02809) with a significance value of 0.474 > 0.05. There is a positive and significant influence of education on family welfare, as shown by the t-value > t-table (3.831 > 2.02809) with a significance value of 0.000 < 0.05. There is no positive and significant influence of the number of family members on family welfare, as indicated by the t-value < t-table (1.938 < 2.02809) with a significance value of 0.060 > 0.05. Simultaneously, there is a positive and significant influence of income, education, and the number of family members on family welfare, as seen from the F-value > F-table (9.725 > 2.87) with a significance value of 0.000 < 0.05. Furthermore, the Adjusted R Square value is 0.402, which means that income, education, and the number of family members account for 40.2% of the influence on family welfare, while the remaining 59.8% is influenced by other variables not included in this study.